Predictive Factors For Conversion Of Laparoscopic Cholecystectomy To Open Procedure - Hawrame, Taher Abdullah; Shareef, Sirwan Hama; Fathalla, Zanko Sherko (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Laparoscopic cholecystectomy is the gold stander surgery for gallbladder diseases, especially symptomatic gall stone disease. to identify the factors that causes the conversion of planed laparoscopic cholecystectomy to an open procedure. Identifying these predictive factors will predict the conversion rate and eventually will help the surgeon, the patient and the hospital in planning the surgery. Methods: Retrospective study. Between October 2003 and December 2004 hundred and fifty patients with symptomatic gallstone underwent laparoscopic cholecystectomy in Department of Surgery, Sulaimaniyah Teaching Hospital Results: ages of the patients were between 11-70 years with a mean of 40, female to male were 5/1, and in 47% the symptoms were present for more than two years. Conversion incidence was 8.7. Conclusion: The predictive factors for conversion in our study accordingly were duration of the symptoms, abnormal intra-abdominal findings, concurrent illnesses, and intra-operative complications.